2015
DOI: 10.1136/bcr-2014-207969
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral eccentric vision training on pseudovitelliform dystrophy with microperimetry biofeedback

Abstract: Low vision patients with eccentric viewing (EV) use extrafoveal retinal areas to compensate for the loss of central vision. Such retinal loci are known as the preferred retinal locus (PRL). It is known that EV is accompanied by unstable fixation. Microperimetry systems with biofeedback training have been used as a rehabilitation aid to improve fixation stability in EV patients. Normally, only the best or dominant eye is selected for such rehabilitation. This case report describes the rehabilitation on both eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Eyes with eccentric fixation regularly demonstrate unstable FS with associated low vision. However, it has been reported that FS can be improved with oculomotor exercises known as biofeedback fixation training (BFT) [6,[9][10][11][12][13], a task-oriented behavioural therapy, which according to some authors may drive neural plasticity changes in the visual system [11,14]. BFT consists of asking patients to perform ocular movements towards a specific direction, attempting to align a selected retinal locus with a visual target.…”
Section: Introductionmentioning
confidence: 99%
“…Eyes with eccentric fixation regularly demonstrate unstable FS with associated low vision. However, it has been reported that FS can be improved with oculomotor exercises known as biofeedback fixation training (BFT) [6,[9][10][11][12][13], a task-oriented behavioural therapy, which according to some authors may drive neural plasticity changes in the visual system [11,14]. BFT consists of asking patients to perform ocular movements towards a specific direction, attempting to align a selected retinal locus with a visual target.…”
Section: Introductionmentioning
confidence: 99%
“…With microperimetry biofeedback training, patients with macular diseases who have lost foveal fixation capabilities are trained to relocate their preferred retinal locus (PRL) into an area with better sensitivity. This training to relocate the PRL can improve the fixation behavior and, thereby, visual performance [21][22][23]24,25]. Several authors have demonstrated that this training is effective in patients with loss of central vision secondary to macular pathologies, particularly in cases with geographic atrophy secondary to AMD [21,23,24,26]; however, it has also been reported that patients with macular disease may use two or more PRLs for fixation [24,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…This training to relocate the PRL can improve the fixation behavior and, thereby, visual performance [21][22][23]24,25]. Several authors have demonstrated that this training is effective in patients with loss of central vision secondary to macular pathologies, particularly in cases with geographic atrophy secondary to AMD [21,23,24,26]; however, it has also been reported that patients with macular disease may use two or more PRLs for fixation [24,25,27]. In our study during three examinations, the fixation stability improved in the better eye of AMD patients, but the stable consistency and accuracy in fixation stability on the same fixation location (same retinal locus/correct choice of the new fixation point [PRL] required more tests and biofeedback trainings.…”
Section: Discussionmentioning
confidence: 99%
“…The patient underwent visual rehabilitation sessions using the training module available in the equipment. Visual rehabilitation program included two training sessions of 10 minutes with 20 minutes time intervals, in the better eye, once a week for 8 weeks as it was described in similar studies [5]. As the result of standard microperimetry examination the new desired fixation point -Preferred Retinal Target (PRT), was selected.…”
Section: Case Descriptionmentioning
confidence: 99%
“…In the absence of retinal macular disease, microperimetry allows accurate study of the effect of secondary retinal sensitivity due to loss of ganglion cells and axons at the level of the papillomacular bundle [4]. Microperimetry systems with biofeedback training have been used for visual rehabilitation and for improving fixation stability in patients with eccentric vision [5].…”
Section: Introductionmentioning
confidence: 99%